DIELECTRIC PROPERTIES OF POLYMER COMPOSITE MATERIALS BASED ON GRAPHITE - and and (Municipal economy of cities (Technical science), 2013)
The results of the study of the effect of graphite content on the thermo insulating properties of linear low-density polyethylene, The mechanism of polarization of the composition. It was established experimentally that increasing the concentration of thermally exfoliated graphite in the polymer composition increases the value of the dielectric constant.